Direct laser powder bed fusion of ceramics - Thywill Cephas Dzogbewu; Deon Johan de Beer (Results in Materials)
Direct laser powder bed fusion (LPBF) of ceramics has experienced tremendous advancement and it is about to be metamorphosed from the laboratory research phase to the industrial scale. Nonetheless, several challenges need to be overcome before progressing to the next phase of manufacturing crack-free, large-size, and multimaterial ceramic products via the direct LPBF process with high surface quality and homogeneous mechanical integrity. Surprising the current challenges required automation of the in-process activities to control the high viscous ceramic molten pool and its solidification mechanisms to mitigate the building up of thermal stress, and crack formation to ensure the production of crack-free, large-size ceramic parts with high surface quality. The automation of the process would ensure consistency, reliability, and reproducibility of direct printing of ceramic products, which would speed up the development of a validation framework for the certification of direct printed ceramic products. The post-processing activities of the indirect ceramic printing process might not be the ideal approach for producing dense crack-free ceramic products, since it could increase the cost of the product by 70 % without any significant improvement as compared to the direct LPBF ceramic manufacturing route.